Altered ellipsoid zone reflectivity and deep capillary plexus rarefaction correlate with progression in Best disease. Issue 4 (29th July 2019) - Romano, Francesco; Arrigo, Alessandro; Leone, Pier Pasquale; Saladino, Andrea; Bandello, Francesco; Battaglia Parodi, Maurizio
Abstract : Aims: To evaluate the effects of neurovascular damage in patients with the typical vitelliform lesion of Best vitelliform macular dystrophy (BVMD) in the attempt to identify different progression patterns. Methods: Prospective, observational case series. Patients in the vitelliform stage of BVMD and healthy controls underwent complete ophthalmological examination on a yearly basis, including best-corrected visual acuity (BCVA), biomicroscopy, optical coherence tomography (OCT) and OCT angiography (OCT-A). 4.5×4.5 mm OCT-A slabs were imported into ImageJ software and their vessel density (VD) was calculated. Similarly, the ellipsoid zone (EZ) was manually outlined and the reflectivity was measured above the vitelliform lesion and in the 500 µm external to it. Retinal pigment epithelium–Bruch's membrane complex was taken as internal reference. Results: 34 eyes (24 patients) and 34 matched controls were included in the study. Mean follow-up was of 28.4±5.8 months, with 12 eyes showing signs of stage progression at the end follow-up. The EZ overlying the vitelliform lesion and in the peri-lesional area disclosed a significant reduction in reflectivity when compared with the foveal and para-foveal EZ of controls, respectively. VD resulted meaningfully decreased only at the deep capillary plexus. Of notice, more extensive EZ (reflectivity <0.7) and vascular alterations (VD <0.4) at baseline strongly correlated with worse BCVA and were associated with a more rapid progression at follow-up. Conclusions: Both EZ reflectivity and VD at deep capillary plexus may prove valuable biomarkers to assess BVMD severity and detect progression. In this view, 'rapid progressors' might benefit the most from timely genetic therapies in the future.